LUNULARIN AND OXYRESVERATROL : TWO STILBENE DERIVATIVES FROM Morus macroura - Nunuk H Soekamto; Sjamsul A Achmad; Emilio L Ghisalberti; Euis H Hakim; Yana M Syah (Indonesian Journal of Chemistry, 2005)
Two stilbene derivatives namely lunularin and oxyresveratrol were isolated from Morus macroura Miq. (Moraceae), a rare spesies found in West Sumatera and endemic to Indonesia. The structure of all these compounds were elucidated based on physical and spectroscopic data.